2019
DOI: 10.1186/s12969-019-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in childhood-onset lupus: results of a multidisciplinary prioritization exercise

Abstract: Background Childhood-onset systemic erythematosus lupus (cSLE) is characterized by more severe disease, widespread organ involvement and higher mortality compared to adult-onset SLE. However, cSLE is largely underfunded to carry out necessary research to advance the field. Few commonly used SLE medications have been studied in children, and important knowledge gaps exist concerning epidemiology, genetics, pathophysiology and optimal treatments for cSLE. Methods In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…16 LN has recently been named a research priority by both CARRA and the Lupus Foundation of America. 17 Since CARRA currently has a robust active cohort of cSLE patients, our aim was to identify traditional principles related to the diagnosis, treatment, and surveillance of LN in childhood and determine if they remain valid in this contemporary multi-center cohort.…”
Section: Introductionmentioning
confidence: 99%
“…16 LN has recently been named a research priority by both CARRA and the Lupus Foundation of America. 17 Since CARRA currently has a robust active cohort of cSLE patients, our aim was to identify traditional principles related to the diagnosis, treatment, and surveillance of LN in childhood and determine if they remain valid in this contemporary multi-center cohort.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been advances in understanding disease mechanisms and treatment of cSLE in the last decade, significant needs remain, underscoring the necessity of a focused research agenda for allocation of available resources. Expanding on the findings from the ALPHA study5 6 and CARRA-LFA survey regarding cSLE research priorities,7 we elucidated approaches to address cSLE research priorities, exploring both barriers and opportunities to advancing cSLE research. Multidisciplinary experts in our study identified research priorities represented by five domains: (1) expanding disease knowledge; (2) investigator collaboration; (3) partnering with patients and families; (4) improving care to optimise research; and (5) overcoming investigator barriers.…”
Section: Discussionmentioning
confidence: 99%
“…To expand on the NIAMS-identified objectives and ALPHA study results, the Childhood Arthritis and Rheumatology Research Alliance (CARRA) and the Lupus Foundation of America (LFA) partnered to identify key knowledge gaps and strategies for advancing cSLE research. An initial objective of this collaboration was to prioritise cSLE research domains by surveying rheumatologists, nephrologists and dermatologists with expertise in cSLE 7. The previously published survey study identified the highest prioritised domains as SLE nephritis, clinical trials, biomarkers, neuropsychiatric disease and refractory skin disease 7…”
Section: Introductionmentioning
confidence: 99%
“…Some participants with mild juvenile arthritis even questioned their ability to have children at all. These issues highlight a critical disconnect between patients’ and clinicians’ priorities and knowledge: reproductive health is not yet routinely addressed as part of transitional care [ 20 ] and ranks low on clinicians’ research priorities [ 21 ]. Reasons why reproductive health inquiry and counseling has not become standard in pediatric subspecialty care is likely multifactorial and is a topic of ongoing research.…”
Section: Discussionmentioning
confidence: 99%